Rhinolithiasis: Two Clinical Cases and Review of the Literature - Campos, Ana; Pais, José; Barreto, Isaulina; Caroça, Cristina; Paço, João (Gazeta Médica, 2020)
Rhinolithiasis is a rare condition and seldom referred in literature. Rinolith is a calcified mass in the nasal cavity. It can be an incidental finding in an asymptomatic patient or a cause of chronic rhinosinusitis with nasal cavity and paranasal sinuses destruction. It is a differential diagnosis in patients suffering from persistent rhinorrhea and nasal obstruction, most commonly unilateral. Nasal endoscopy and computed tomography are essential tools for the diagnosis. The treatment consists of surgical removal, which can be done under local or general anesthesia, by endoscopic or external approach. The authors present two clinical cases that illustrate different kinds of this pathology and make a literature review of it.